PENGARUH PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN SEPATU FUTSAL MEREK SPECS (STUDI KASUS UKOM FUTSAL UNIVERSITAS KRISTEN INDONESIA) - Salma Reza Safira; Rutman Lumbantoruan; Sinaga, Sautman (Universitas Kristen Indonesia, 2023)
This research study was carried out in order to be able to provide information related to the impact that arises from product and price influences on the purchasing decision of futsal shoes with the Specs trademark purchased by Indonesian Christian University UKOM Futsal students. The way to get field data from this research study is to give a questionnaire sheet to the respondents to fill in according to their respective choices. Students of Ukom Futsal Christian University of Indonesia are the population of this research study and the number of samples used to provide answers to the questionnaire questions is 58 respondents. The study sample was found using a purposive sampling method. Product and price are the independent variables of this study, the dependent variable used is purchasing decisions. Testing the field data that has been obtained uses the help of SPSS. A complete statistical test is used for the validity of the data obtained. Processing of field data obtained the following results: (1) there was a product influence on the purchasing decision of the Specs brand futsal shoes at Ukom Futsal UKI. (2) there is a price effect on the purchasing decision of Specs brand futsal shoes at Ukom Futsal UKI. (3) there is an influence of product and price on the purchasing decision of the Specs brand futsal shoes of 83.6%. In accordance with the field findings, the suggestion for the company is to complete the collection of goods and expand the reach of the marketing area. Keywords: Product, Price, Purchase Decision